Análisis y elaboración de una base de datos realizada según el censo de equipos electrónicos para uso médico del hospital león becerra de Milagro - Ganchozo López, José (2009)
This graduation project has two main objectives: The first objective is to realize a poll to the Administrator and the Maintenance Manager of the Hospital “León Becerra” of Milagro and the second objective is to develop a database of the hospital equipment. This topic consists of two parts. The first one is a poll to directives of the Hospital “León Becerra” of Milagros in order to know about the level of service offered to the users, which takes as a reference standards, codes and policies in the areas of electrical, mechanical, environmental, biological, radioactive and electromagnetic safety. The second part is based on a census of electronic equipment for medical use in the same hospital, with the aim to recognize the equipment level of different areas and the services it can provide to the community. This work can be also used to determine the causes of damage of the electronic equipment for medical use.